HOW DOES THE AGRICULTURAL SECTOR AFFECT THE ECONOMIC GROWTH OF DEMAK REGENCY? - Caroline Soekarno; Soni Agus Irwandi; Siti Sumiati; Sri Umiatun (Jurnal REP (Riset Ekonomi Pembangunan), 2024)
This research is motivated by the phenomenon that the area of ​​agricultural land in Demak Regency has changed the function of the land, from paddy fields to non-rice fields in the form of housing and industry. Changes in land use are thought to be due to rob, abrasion, land acquisition for the Semarang-Demak toll road. The agricultural sector was originally the leading sector/base sector in Demak Regency, then slowly shifted to the industrial sector. The purpose of this study was to analyze the performance of the agricultural sector in Demak Regency. This research method uses SWOT analysis which has been modified by using the Demak Regency stakeholder questionnaire and spatial data analysis approach using maps processed by GeoDa. The results of the analysis show that from 2017 to 2021, Demak Regency, based on the Klasson Typology, is included in the criteria for a developed but depressed area. This means that the economic growth of Demak Regency is developing in accordance with the existing geographical conditions. The superior agricultural production in Demak Regency is rice, corn, sweet potato, cassava, peanuts, green beans, soybeans, and cassava sorghum. Based on a SWOT analysis with threats to the agricultural sector in Demak Regency in the form of ROB floods, abrasion, reduced use of paddy fields to non-rice fields, prices of agricultural products that do not break even point, Demak Regency policies adopting agricultural intensification strategies, and agricultural extensification policies.